2007
DOI: 10.1196/annals.1392.013
|View full text |Cite
|
Sign up to set email alerts
|

AMD3100 and CD26 Modulate Mobilization, Engraftment, and Survival of Hematopoietic Stem and Progenitor Cells Mediated by the SDF‐1/CXCL12‐CXCR4 Axis

Abstract: The chemokine stromal cell-derived factor-1 (SDF-1/CXCL12) and its receptor, CXCR4, are involved in a number of facets of the regulation of hematopoiesis at the level of hematopoietic stem (HSCs) and progenitor (HPCs) cells. Modulation of this ligand-receptor interaction may be of clinical utility. We now report that: (1) the CC chemokine, macrophage inflammatory protein-1alpha (MIP-1alpha/CCL3) synergizes with AMD3100 (an antagonist of the binding of SDF-1/CXCL12 to CXCR4) to rapidly mobilize HPCs to the bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 49 publications
(117 reference statements)
2
75
1
3
Order By: Relevance
“…13,14,23,24,26 A dose-related increase in hematopoietic progenitor cells, colony forming unit-granulocyte macrophage, colony forming unit-granulocyte erythroid macrophage megakaryocyte and burst-forming unit-erythroid was seen in healthy volunteers at doses of 80, 160, 240 mg/kg. The synergistic effect of plerixafor and G-CSF has been examined in preclinical models, 17 healthy volunteers 18,23 and in patients with multiple myeloma or non-Hodgkin's lymphoma. 19,21,[24][25][26] These studies showed that there is a Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14,23,24,26 A dose-related increase in hematopoietic progenitor cells, colony forming unit-granulocyte macrophage, colony forming unit-granulocyte erythroid macrophage megakaryocyte and burst-forming unit-erythroid was seen in healthy volunteers at doses of 80, 160, 240 mg/kg. The synergistic effect of plerixafor and G-CSF has been examined in preclinical models, 17 healthy volunteers 18,23 and in patients with multiple myeloma or non-Hodgkin's lymphoma. 19,21,[24][25][26] These studies showed that there is a Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Subsequently, the role of plerixafor in the mobilization of PBSCs for auto-SCT was explored. 16,17 Plerixafor has been shown to rapidly increase circulating CD34 þ progenitor cells in preclinical murine models and healthy volunteers alone or in combination with G-CSF. [17][18][19] Other clinical trials were performed combining plerixafor and G-CSF for multiple myeloma or non-Hodgkin's lymphoma patients in first or second complete or PR planned for auto-SCT.…”
Section: Introductionmentioning
confidence: 99%
“…12,14,15 Bone marrow trophic, hypoxic pockets attract and retain HSC indirectly via HIF-1 among other paths. 14,16,17 HIF-1 to CXCR4-CXCL12 system CXCR4 is a 45 kDa outer cell membrane receptor for the 8 kDa chemokine CXCL12 (synonymous with the older term stromal-derived factor-1). 16,17,18 HIF-1 interacts with the promoter region of the CXCR4 gene, stimulating its transcription 19,20 and with the promoter region of the CXCL12 gene, stimulating its transcription.…”
Section: Introductionmentioning
confidence: 99%
“…14,16,17 HIF-1 to CXCR4-CXCL12 system CXCR4 is a 45 kDa outer cell membrane receptor for the 8 kDa chemokine CXCL12 (synonymous with the older term stromal-derived factor-1). 16,17,18 HIF-1 interacts with the promoter region of the CXCR4 gene, stimulating its transcription 19,20 and with the promoter region of the CXCL12 gene, stimulating its transcription. 21,22 HIF-1 also upregulates vascular endothelial growth factor expression 23,24 contributing to marrow neoangiogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation